2015
DOI: 10.7314/apjcp.2014.15.24.10867
|View full text |Cite
|
Sign up to set email alerts
|

Educational Levels and Delays in Start of Treatment for Head and Neck Cancers in North-East India

Abstract: Background: There are various patient and professional factors responsible for the delay in start of treatment (SOT) for head and neck cancers (HNC). Materials and Methods: This retrospective study was conducted on data for HNC patients registered at the hospital cancer registry in North-East India. All cases diagnosed during the period of January 2010 to December 2012 were considered for the present analysis. Educational levels of all patients were clustered into 3 groups; illiterates (unable to read or write… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 10 publications
2
6
0
1
Order By: Relevance
“…So, it must be borne in mind before interpreting the results from this study, as it has not taken into account patients with disabilities or with poor general conditions from rural or urban areas. It has been previously shown that higher educational levels have a positive influence for the start of treatment in patients with HNC (Krishnatreya et al, 2014). Our present survey has shown that literacy is significantly associated with reduction in the median patient delay in HNC.…”
Section: Discussionsupporting
confidence: 62%
“…So, it must be borne in mind before interpreting the results from this study, as it has not taken into account patients with disabilities or with poor general conditions from rural or urban areas. It has been previously shown that higher educational levels have a positive influence for the start of treatment in patients with HNC (Krishnatreya et al, 2014). Our present survey has shown that literacy is significantly associated with reduction in the median patient delay in HNC.…”
Section: Discussionsupporting
confidence: 62%
“…Zeynep Temiz 1 , Didem Ozturk 2 *, Gulay Altun Ugras 3 , Seher Deniz Oztekin 2 , Emel Sengul 4 post-operative individual needs of patients (Sendir, Buyukyılmaz and Musovi, 2003;Johansson et al, 2007;Falvo, 2011;Galdeano et al, 2014;Krishnatreya et al, 2014). It has been reported in the literature that patients obtaining information specific to their health condition experience an accelerated healing process, show better compliance to treatment, have increased self-confidence, satisfaction, coping skills, and quality of life and decreased anxiety and unplanned medical visits, which in turn reduces health care costs and increases the quality of health care (Clark et al, 2005;Mcmurray et al, 2007;Piredda et al, 2008;Williams, 2008;Myers and Pellino, 2009;Fedai, Cetin and Teke, 2010).…”
Section: Determination Of Patient Learning Needs After Thyroidectomymentioning
confidence: 99%
“…Krishnatreya et al has also studied that there was significant difference in educational level of patient and start of treatment in head and neck cancer. 10 Tiwari et al reported that in their study 77.87% of the patients with little or no education presented in advanced stages of the disease. 15 In present study 50 % of patients had Lyratzopoulos et al, reported that socioeconomic inequalities was associated with delayed in diagnosis.…”
Section: Discussionmentioning
confidence: 86%
“…Krishnatreya et al mentioned that literacy rates have also been indirectly related to the socio-economic condition of the patients causing delayed presentations. 10 Factors such as educational levels, availability of treatment resources and knowledge regarding cancer issues to be important factors affecting the delays. 11,12 At our institute more than 80% patients of cancer present in very advanced stages when treatment options are limited and most of them are managed by palliative intent.…”
mentioning
confidence: 99%